Age-dependent changes of antler size in red deer in two contrasting habitats in Hungary - Kolejanisz Tamás (Review on agriculture and rural development, 2012)
The purpose of the study was to analyse age-dependent changes of antler size in red deer (Cervus elaphus) in two contrasting habitats. The study involves the area of Gemenc-Hajós ("excellent habitat") and the Börzsöny Mountains ("poor habitat"). We statistically analysed the trophy evaluation data, population estimates and harvest data of local game management units. We also compared the two study areas on the basis of the most important antler characteristics of different age groups (antler mass, antler length, number of antler tines). Mean antler masses in the area of GemencHajós exceeded that of in Börzsöny Mountains during the entire study period. The difference is insignificant in the case of young stags; however, considering the middle-aged, even more the old age groups, the agedependent deviations of the averages between the two different habitats show an increasing trend. The differences in the mean antler lengths show a similar trend, however, the growth is not as considerable as in the antler masses. In turn, considering young stags the differences are negligible. Finally, taking into account the mean number of tines, we can report similar differences as in the case of antler lengths. The results indicate that antler sizes of young stags shot in the area of Gemenc-Hajós on average are very similar to that of the stags shot in the Börzsöny Mountains, which can be attributed to the contrasting habitats and the diverse harvest per age group. From the middle-age the differences of averages are increasing as the better habitat allows red deer stags to develop larges antlers.